Análisis de las políticas y programas de prevención para la violencia intrafamiliar en las mujeres del cantón quevedo año 2023 - Santana Coello, Carlos Alberto (2025)
Domestic violence is a complex phenomenon that affects thousands of women in Ecuador, generating devastating effects at both the individual and social levels. Despite government efforts to implement prevention policies and programs, domestic violence remains a persistent problem, particularly in rural and marginalized urban areas such as the Quevedo canton, located in the Los Ríos province. This study aims to analyze public policies and intervention programs implemented in Quevedo, in order to evaluate their effectiveness, identify the barriers that limit their implementation, and propose measures to improve their reach and impact. A mixed methodological approach was used, combining qualitative and quantitative data collection through interviews with key stakeholders (such as local authorities and representatives of social organizations) and surveys of women victims of violence. In addition, a documentary analysis of public policies and prevention programs in the Quevedo canton was conducted. The results revealed that, despite the existence of preventive policies, they present significant deficiencies, such as a lack of resources, a cultural resistance to reporting, and poor inter-institutional coordination between the entities responsible for their implementation. The study also underscores the importance of adopting a comprehensive approach that combines social awareness, strengthening protection institutions, and creating community support networks.